Scenarion Planning Development of PT. Krakatau Posco - Siregar, Lukman; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2019)
Abstract - Steel industry is an industry that has lots of uncertain factors. Some of uncertain factors that give impact to the steel industry are demand volatility, continuous overcapacity, and increased volatility in raw material prices. Rising trade tension and volatile currency movement are further increasing the uncertainty. Krakatau Posco, as one of the major steel producers in Indonesia is playing an important role in the success of the country’s national plan to reduce dependency on the steel imports in the future. Therefore, Krakatau Posco needs a comprehensive strategy formulation process based on the long-run understanding of the future. This final assignment is focused on the developing of a scenario planning as a vision and insight for Krakatau Posco’s decision maker to challenge the current thinking about the long-term strategy agenda of the company. As the result finding, raw material prices and government support become the most two critical and uncertain factors for Krakatau Posco to consider in the long run. These two factors create scenario matrix and form four plausible scenarios, they are Raw Material Chaotic, Steel Survival, The Lobbying, and Steel is King. Implication and options from each scenario are explored to identify alternative strategies. Furthermore, early warning signals are identified to address the movement of current condition toward one scenario or another. As the conclusion of this research, three strategic imperatives are defined as. They are long-term contract of raw material supply, creation of government relationship task force, and expansion of raw material storage capacity. Keywords : Steel Industry, Scenario Planning, Strategic Decision Making, Krakatau Posco